2019
DOI: 10.1186/s41100-019-0234-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peritoneal dialysis and hemodialysis as first renal replacement therapy in patients with end-stage renal disease and diabetes: a systematic review

Abstract: Background: Diabetes has become the most common cause of end-stage renal disease (ESRD) requiring renal replacement therapy (RRT) in most countries around the world. Peritoneal dialysis (PD) is valuable for patients newly requiring RRT because of the preservation of residual renal function (RRF), higher quality of life, and hemodynamic stability in comparison with hemodialysis (HD). A previous systematic review produced conflicting results regarding patient survival. As several advances have been made in thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Peritoneal dialysis (PD) is a safe life-sustaining renal replacement modality, employed for the treatment of end-stage renal disease (ESRD) worldwide. According to the last registry, 11% of the global dialysis population is under PD [1][2][3]. In many countries, patient outcomes with PD are comparable to or better than those with hemodialysis, and PD is also more cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal dialysis (PD) is a safe life-sustaining renal replacement modality, employed for the treatment of end-stage renal disease (ESRD) worldwide. According to the last registry, 11% of the global dialysis population is under PD [1][2][3]. In many countries, patient outcomes with PD are comparable to or better than those with hemodialysis, and PD is also more cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic patients were less likely to receive PD as first RRT than nondiabetic patients in Europe (26,27,29). The presence of diabetic retinopathy and peripheral neuropathy, anxiety about poorer glycemic control, and increased risk for peritonitis may be the underlying reasons (29). Transfer to HD may be more common in diabetic PD patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that both age and the presence or absence of diabetes were the main factors that contributed to the survival difference between PD and HD therapy. [15][16][17] Generally, PD therapy seemed to be associated with an equal or better survival in younger patients, but inferior to HD therapy in elderly diabetic patients. [18][19][20][21][22] In the present study, we stratified patients into four groups based on age and the presence of DN.…”
Section: Discussionmentioning
confidence: 99%